Legal Regulation of Tax Advisory Services In Relation To Their Quality - Čokelc, Stanko; Oplotnik, Žan Jan (Naše gospodarstvo/Our economy, 2012)
This article analyzes the suitability of the legal regulation of tax advisory services in relation to their quality based on our comparative analysis of the (non)regulation of tax advisory services in selected EU states, our analysis of the existing regulatory framework in Slovenia, as well as stakeholders’ opinions. We use the results of all three analyses to propose an optimal model of regulation of the profession and the level of regulation, centred on the need to ensure quality services for clients, service providers, the state, and society as a whole. The key finding is that greater regula- tion would improve the quality of tax advisory services, which is important not only for clients of services, but also the public interest as it increases confidence in tax re- turns and financial statements prepared by tax advisors, which in turn improves the economy and mitigates operative risks.
Keywords: tax; tax advisory services; regulated professions; quality of services